Implementation of Environment-Friendly Strategies for Energy Conservation and Mitigation of Climate Change – A Holistic Approach in Mangalagangotri Campus - P. Subrahmanya Yadapadithaya; Prashantha Naik; Kishori Nayak K. (Universitas Diponegoro, 2022)
The harnessing of renewable energies and mitigation of climate change are like two faces of a coin. Decentralized implementation and individual-level practices of eco-friendly strategies contribute a lot on a global scale. In this context, Mangalore University on its headquarters Mangalagangotri campus, adopted and implemented many eco-friendly activities, technologies, and policies for sustainable development. Installation of solar power panels for electricity generation, of the current estimated value of 23,13,311 kWh/month; replacement of incandescent bulbs with LED bulbs with an energy saving of around 62% and procurement of most energy-efficient electronic & electrical appliances (47%) are some of the technologies that have been implemented for energy conservation. Implementation of e-Governance and e-Office program of Govt of Karnataka, and campus management system, social media, and email-based official communications have significantly reduced the usage of papers (>70% ); a complete ban on single-use plastics; recycling of organic wastes through vermicomposting, pot-composting, biogas production; encouraging electric vehicles are some of the adopted strategies. Altogether these strategies have significantly reduced the release of greenhouse gases in and around the campus in our efforts to join with global efforts to drop carbon footprint below 2 tons by 2050. The rainwater harvesting through the rooftop catchments and check-dams contributed to ≈ 50% water conservation. The campus comprises 32.4% of its total area with natural vegetation (463192 m2) and currently with 30.8% planted vegetation (439670 m2) of the total area (1428540 m2). The campus biodiversity was further enriched by periodical tree plantation drives with special reference to the planting of fruit-yielding saplings. As an Institutional Social Responsibility (ISR), the university has been making efforts to disseminate the knowledge of eco-friendly practices, by conducting public awareness programs and publishing popular articles in regional language. Despite the COVID-19 pandemic and government-imposed lockdown to curb the spread of the novel coronavirus, the University has continued eco-friendly activities and setting up of infrastructures, by strictly following safety guidelines. Overall, our continued holistic approaches of various eco-friendly strategies, in terms of the utility of advanced technologies, eGovernance, solar energy, and rainwater harvesting, organic wastes management, recycling of solid wastes, and many others, have been implemented since its inception have significantly helped in saving energy and reduction in the emission of greenhouse gases.Keyword: Climate change; Eco-friendly strategies; Carbon footprint; Greenhouse gases